Factors influencing spiritual needs in patients with chronic diseases: A systematic literature review - Fatahillah Syafruddin; Riri Maria; Anggri Noorana Zahra (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Spiritual needs are a critical component of holistic care for patients with life-threatening illnesses, yet their manifestation varies significantly across different disease pathways. Purpose: To identify and synthesize the multifaceted factors influencing spiritual needs in patients with cancer, cardiovascular disease (CVD), chronic kidney disease (CKD), and stroke, while mapping how different clinical trajectories contribute to variations in spiritual experiences. Method: Following PRISMA 2020 guidelines, a systematic search was conducted in Scopus and PubMed for primary empirical studies published between 2020 and 2026. A total of 398 records were identified, and after rigorous screening and quality assessment, 49 studies were included in the final synthesis. Results: Spiritual needs among patients with chronic diseases: cancer, cardiovascular disease, chronic kidney disease, and stroke are associated with interconnected clinical, demographic, physical, psychological, psychosocial, socioeconomic, and cultural factors. Disease burden, physical symptoms, psychological distress, social support, and personal beliefs collectively shape spiritual well-being, highlighting its dynamic nature throughout the illness trajectory. Conclusion: Spiritual needs among patients with chronic and life-threatening illnesses are associated with clinical, demographic, physical, psychological, psychosocial, socioeconomic, and spiritual-cultural factors. Integrating routine spiritual assessment and personalized spiritual care into healthcare practice may help improve coping, resilience, and quality of life.